Risk capital in unit-linked insurance policies - Homa, Magdalena (Research Papers of Wrocław University of Economics, 2018)
Unit-linked insurance policies (ULIP) are endowment policies with shares in selected investment funds held by financial institutions, which combine insurance coverage with investment. Therefore, the risk related to this type of insurance is analysed as: subject of insurance risk and financial risk which determine the value of ULIP. To secure its liquidity, the insurer should take this enhanced risk. Thus, the aim of this text is to determine the appropriate capital levels which should offset the additional risk to which the insurer is exposed to in order to ensure the financial security of the insured persons and protect the insurer’s solvency
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2018, Nr 519, s. 99-108
Keywords: unit-linked insurance; Solvency II; risk capital; Monte-Carlo; ubezpieczenia UFK (unit-linked); kapitał podwyższonego ryzyka; metoda Monte Carlo